The Effect of Welfare and Leadership Style on Performance of 725/Woroagi Battalion Personnel in The Framework of Ri-PNG Pamtas Task Force in the 2022-2023 Academic Year - Waskito, Susilo; Kalsum, Ummy; Lisapaly, David C.E. (International Journal of Management and Education in Human Development, 2024)
This research aims to test and explain: (1) The influence of welfare and leadership style on the performance of Yonif 725/Woroagi personnel in the framework of the RI-PNG PAMTAS TASK AS 2022-2023. (2) The influence of welfare on the performance of Yonif 725/Woroagi personnel in the context of the RI-PNG PAMTAS TASK FY 2022-2023. (3) The influence of leadership style on the performance of Yonif 725/Woroagi personnel in the framework of the RI-PNG PAMTAS TASK AS 2022-2023. This research design is a survey with an explanatory research design. Data collection was carried out using a survey method using an instrument in the form of a questionnaire. The population of this study was all personnel from Yonif 725/Woroagi SATGAS PAMTASRI-PNG FY 2022-2023, totaling 450 people. The sample was determined using the Slovin formula with a precision of 10%, resulting in a total sample of 82 people. The analysis equipment used is Multivariate Regression Analysis. The research results show that (1) welfare and leadership style simultaneously have a significant effect on personnel performance. (2) welfare partially has a positive and significant effect on personnel performance. (3) Leadership style partially has a positive and significant effect on personnel performance. Thus, it can be concluded that changes in improving welfare and leadership style have a positive and significant contribution to improving personnel performance.